Miejsce melancholii w kulturze staropolskiej w świetle kazań pogrzebowych przełomu XVII i XVIII w. = Place of melancholy in Old Polish culture in the light of the funeral sermons in the turn of 17th and 18th century - Bąk, Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Melancholy is a concept of a rich semantic structure. Old Polish concept of melancholy was formed under the influence of ideological currents of the era and served mainly as the expression of thought and reflection on the passing time, in which the phenomenon of death played a key role. In the Middle Ages the term of melancholy, known as acedia at that time, was perceived as a sin. For a man of the Baroque death was the harbinger of eternal life, which is why his attention was firmly focused on eschatological concepts.
Keywords: melancholia; kazania pogrzebowe; Polska - kultura - 17-18 w.